Dualistic perspectives on illness coping experiences of individuals with depression and their spouses: a qualitative study - Xiaoli Cheng; Liping Liu; Shifen Ni; Chuansu Li; Hongyin Zhang; Bo Mao; Jing Zeng (International Journal of Qualitative Studies on Health & Well-Being)
Purpose Dyadic coping interventions alleviate emotional problems in patients and families with a variety of chronic illnesses. Current coping research on depression focuses mainly on the individual level. This study examined the experiences of people with depression and their spouses, using a dyadic coping perspective to support the implementation of a targeted dyadic intervention. Method Semi-structured, in-depth interviews were conducted with patients with depression and their spouses. The data were organized and analysed using Colaizzi’s seven-step method. Results The experiences of individuals with depression and their spouses were categorized into four themes and 12 subthemes: delays in medical care (delays in medical decision-making, delays in in-hospital care), spousal maladjustment (perceived stress of the illness, role conflict, negative emotions), coexistence of positive and negative dyadic coping strategies (shared coping, positive communication, emotional support, negative communication, overprotectiveness), and confusion and needs (fear of illness prognosis, desire for continuity of care). Conclusion Healthcare professionals should promote positive dyadic coping among individuals with depression and their spouses while caring for depressive illnesses. They should strengthen individuals’ knowledge of the disease, attend to spouses’ physical and mental health, explore couple-centred dyadic intervention strategies, and improve continuity in the healthcare system.